2020
DOI: 10.1016/j.chempr.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed C−H Functionalization Using A Non-directed Strategy

Abstract: The activation of ubiquitous C-H bonds has great significance in the field of organic synthesis given that it represents an ideal method for directly producing valuable chemicals from structurally simple compounds. First-row transition metals have recently been recognized as a potential alternative to noble transition metals because of their low cost, unique reactivity profiles, and easy availability. Among these metals, nickel (Ni) catalysts have drawn considerable attention from the scientific community. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
65
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(65 citation statements)
references
References 151 publications
(158 reference statements)
0
65
0
Order By: Relevance
“…Moreover, the reaction takes place by utilizing benzene-1,3,5-triyl triformate (TFBen) as an easily handled, solid carbon monoxide source and the acidic additive PivOH which promotes the reaction to higher yields by most likely generating the active Co species and possibly aiding the removal of the TDG. Higher yields are also observed when using Et 3 N and 1,4-dioxane at 130 • C for prolonged reaction time, even though 50% conversion was achieved after 1 h. Under the optimized conditions, structurally diverse naphthylamides were tested and it was observed that a naphthylamide with a methyl group at the C2 position led to only traces of the product, implying that steric hinderance has a detrimental effect (116). On the other hand, when the C4 position of the naphthylamide is substituted, the isolated yields are moderate to high for substrates bearing substituents that are electron-donating (117) or electron-withdrawing (118), phenyl groups bearing either electron-withdrawing or -donating moieties (119)(120)(121), naphthyl groups (122), five-membered aromatic rings (123), and a synthetically valuable alkyne unit (124).…”
Section: C-h Carbonylation With Tdgsmentioning
confidence: 98%
“…Moreover, the reaction takes place by utilizing benzene-1,3,5-triyl triformate (TFBen) as an easily handled, solid carbon monoxide source and the acidic additive PivOH which promotes the reaction to higher yields by most likely generating the active Co species and possibly aiding the removal of the TDG. Higher yields are also observed when using Et 3 N and 1,4-dioxane at 130 • C for prolonged reaction time, even though 50% conversion was achieved after 1 h. Under the optimized conditions, structurally diverse naphthylamides were tested and it was observed that a naphthylamide with a methyl group at the C2 position led to only traces of the product, implying that steric hinderance has a detrimental effect (116). On the other hand, when the C4 position of the naphthylamide is substituted, the isolated yields are moderate to high for substrates bearing substituents that are electron-donating (117) or electron-withdrawing (118), phenyl groups bearing either electron-withdrawing or -donating moieties (119)(120)(121), naphthyl groups (122), five-membered aromatic rings (123), and a synthetically valuable alkyne unit (124).…”
Section: C-h Carbonylation With Tdgsmentioning
confidence: 98%
“…Following the seminal work disclosed by the research groups of Guimond, Fagnou, and Glorius, [1] to date,atremendous number of transition-metal-catalyzed C À Hf unctionalization reactions of arenes with alkynes has been extensively explored and thus far established as an advantageous strategy to build C(sp 2 )-C(sp 2 )b onds. [2,3] With these great advances, many functionalized alkynes and their equivalents have been intensively developed to further strengthen the special topic, especially to improve the regioselective issue existed in asymmetric internal alkynes-involved C À Ha ctivation reactions. [4] Among them, the introduction of fluorinated alkynes as innovative coupling partners has attracted increasing interest from the synthetic community since it exhibits notable features over the traditional alkynes:a)the incorporation of fluorine into organic molecule has been shown numerous times to improve physiochemical and pharmacodynamic properties; [5] b) it not only delivers the extraordinary reaction mode induced by fluorine effects but also endows an accessible reactivity and exclusive regioselectivity engendered by the unique electronic and steric characteristics of the fluorine atom; [6] and c) aredox-neutral catalytic mode can be addressed through the site-/regioselective b-F elimination process,t hus resulting in straightforward access to the target product in amore green and sustainable fashion.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, transition metal-catalyzed inert CÀ H bond functionalization has rapidly evolved as a sustainable and reliable tool for the formation of new CÀ C and CÀ X bonds from structurally simple starting materials without tedious pre-derivation. [8] Motivated by the aforementioned background and based on our recent studies on the synthesis of privileged heterocyclic systems by taking advantages of inert CÀ H bond functionalization, [9] we have designed and studied the reaction of 1-phenylpyrazolidinones [10] with α,αdifluoromethylene alkynes. [11,12] From this study, we were able to develop a novel and efficient approach toward 3-(α-fluorovinyl)indoles and related derivatives (Scheme 1e).…”
mentioning
confidence: 99%